Distribution of amphibians along an elevation gradient in the Eastern Himalaya, india - Chettri, Basundhara; Acharya, Bhoj Kumar (Basic and applied ecology, 2020)
Distribution of biodiversity along the elevation gradient have been a subject of curiosity and a much argued topic in macroecology. Despite considerable attention, there is a lack of consensus on the pattern and the causal factors across regions and taxa. We studied amphibian distribution along the elevational gradient in Sikkim, Eastern Himalaya, part of a globally significant biodiversity hotspot. We conducted intensive field studies covering 300–4600 m elevation using Visual Encounter Survey and Night Stream Survey methods. We examined the effects of both spatial factors (area and mid-domain effect) and environmental variables (temperature, precipitation, moisture, potential evapotranspiration and actual evapotranspiration) on the distribution of amphibians along the elevational gradient. We recorded 25 species and 1368 individuals of amphibians after 1236 man-hours of visual encounter survey and 27 km night stream survey. Species richness of total amphibians and their sub groups (endemic, non-endemic, large-range and small-range) followed unimodal pattern showing a peak at middle elevation but with slight shift towards higher elevation for endemic species. Various environmental variables, especially actual evapotranspiration and mean annual precipitation, explained the elevational distribution trend of amphibians in the Eastern Himalaya. Spatial factors played no significant role in shaping the pattern of amphibian distribution (except endemics and large-range species showing fit to mid-domain effect). Local communities of the study area extract amphibians for food and medicine, especially from the diverse mid elevation zone, which should be closely monitored and curbed by the wildlife authorities.